When Work Conflicts With Personal Projects: The Association of Work-Life Conflict With Worker Wellbeing and the Mediating Role of Mindfulness - Pacheco, Tyler; Coulombe, Simon; Meunier, Sophie (Frontiers in Psychology, 2021)
The negative emotional and health effects of work-life conflict (WLC) have been demonstrated in numerous organizational psychology and occupational health studies. However, little is known about WLC’s relationship with positive wellbeing outcomes, including emotional, psychological, and social aspects of workers' thriving. Furthermore, the mediating processes underlying the effects of WLC remain mostly unknown. The current study investigated the associations of perceived time- and strain-based WLC with positive mental health and thriving at work, as well as the mediating role of mindfulness in these associations. It is argued that WLC causes reduced mindfulness capacities among workers, which is in turn associated with lower positive wellbeing given the importance of mindfulness in emotion regulation. A sample of 330 workers based in Québec, Canada, completed an online survey including a measure of strain- and time-based interference with personal projects (i.e., the goals and activities that define the daily life of an individual) and validated scales of wellbeing outcomes and mindfulness. Results of structural equation modeling revealed negative associations between time- and strain-based WLC with positive mental health and thriving at work. Work-life conflict was related to lower mindfulness, which played a mediating role in the associations between time-based WLC with positive mental health and thriving at work, as well as strain-based WLC with positive mental health. The mediation was complete for the WLC-positive mental health association, but partial for the other mediated pathways, highlighting the need for more research to identify additional mediators. These results highlight that beyond resulting in negative emotional/health outcomes often studied in previous research, WLC may be associated with workers’ potential to live a fulfilling life, in general and in the workplace. Recommendations (e.g., mindfulness intervention to promote emotional regulation, personal project intervention) for workplace policy-makers and practitioners are identified.